Former soap factory 'De Adelaar' in Wormerveer saved (Bulletin KNOB, 1999)
In the village of Wormerveer situated on the Zaan there is a prominent factory building: the former soap factory 'De Adelaar' (The Eagle). The concrete sculpture of an eagle with spread wings - on top of the watertower - is visible for miles around. De Adelaar was built after a design from 1906 and thus is one of the earliest examples in the Netherlands of the use of a reinforced non-supporting concrete skeleton.However, De Adelaar is not only interesting because of its construction. The architects of the building, Jan Paul Frederik van Rossem (1854-1918) and Willem Johannes Vuyk (1855-1918) designed a considerable number of factory buildings, notably in the Zaan region, in the decades around the turn of the century. Some of them, from the period 1902-1915, have many similarities to De Adelaar.For the likewise brick facades of the buildings Hollandia, Java, Rehoboth and Phoenix,Van Rossem and Vuyk used the same interrupted dripstone labels as in the facade of De Adelaar on Zaandijkerweg. This resulted in strikingly designed facades, consisting of wall spaces staggered in relation to each other.Although De Adelaar has had the status of a provincial monument for years, it is not until now that the restoration of the building, which is in rather bad condition, got off the ground. However, a new use for a public function, as was recently proposed, will be out of question. The building will continue to be in use by the owner Loders Croklaan and in all probability it will get a simple body-restoration.